1994
DOI: 10.1302/0301-620x.76b1.8300682
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of uncemented alumina acetabular implants

Abstract: We report the clinical and tribological performance of 67 ceramic acetabular prostheses implanted between 1976 and 1979 without bone cement. They articulated with ceramic femoral heads mounted on mental femoral stems. After a mean elapsed period of 144 months, 59 sockets were radiographically stable but two showed early signs and six showed late signs of loosening. Four of the loose sockets have been revised. Histological analysis of the retrieved tissue showed a fibrous membrane around all the implants, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
56
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(58 citation statements)
references
References 0 publications
1
56
0
1
Order By: Relevance
“…There are no unstable shells or pending failures in the ceramic group at 10 years. Alumina-ceramic bearings have a history of problems with neck/socket impingement, a potential for fracture, and aseptic loosening [2,16,21,30,37]. Considering survivorship revision for any reason, our ceramic cohorts had a survivorship of 95% and 98% and is similar to those of recent publications and may reflect improvements in implant design and the material properties of the ceramic [7,20].…”
Section: Discussionsupporting
confidence: 71%
“…There are no unstable shells or pending failures in the ceramic group at 10 years. Alumina-ceramic bearings have a history of problems with neck/socket impingement, a potential for fracture, and aseptic loosening [2,16,21,30,37]. Considering survivorship revision for any reason, our ceramic cohorts had a survivorship of 95% and 98% and is similar to those of recent publications and may reflect improvements in implant design and the material properties of the ceramic [7,20].…”
Section: Discussionsupporting
confidence: 71%
“…To reduce wear, Boutin [7] reported the use of alumina-on-alumina bearing surfaces in total hip arthroplasty (THA) in 1972. There have been many subsequent reports [3,4,9,12,18,19,25,31,32] regarding the use of ceramic total hip systems. In principle ceramics have the potential for low rates of wear compared to metal-on-polyethylene, and in one study alumina-ceramic bearings demonstrated the lowest rates of in vivo wear as compared with metal -polyethylene combination [20].…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19][20][21][22][23] Light-microscope studies of membranes around revised ceramic THRs reported sizes of alumina particle of between 1 and 3 m which is similar to the grain size of alumina used for production. 15,24,25 Since a size of 1 m is at the lower limit for light microscopy, more sensitive methods have been developed to evaluate submicron debris in tissue membranes. …”
mentioning
confidence: 99%